Multiple autoimmune disorders refractory to glucocorticoids after allogeneic hematopoietic stem cell transplantation: a case report and review of the literature - Xie, Linjun; Xu, Jingjing; Xu, Huiping; Zhang, Beibei; Lin, Wuqiang; Yang, Ting (Frontiers in Immunology, 2024)
We report here the case of a 50-year-old man who was first diagnosed with myelodysplastic syndrome with excess blasts-2 (MDS-EB-2) and underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT) in 2019, resulting in complete remission. However, he was diagnosed in 2021 with several autoimmune disorders, including autoimmune hepatitis (AIH), Hashimoto’s thyroiditis (HT), and autoimmune hemolytic anemia (AIHA). This is referred as multiple autoimmune syndrome (MAS), which is a rare occurrence after allo-HSCT, as previously noted in the literature. Despite being treated with glucocorticoids, cyclosporine A, and other medications, the patient did not fully recover. To address the glucocorticoid-refractory MAS, a four-week course of rituximab (RTX) at a weekly dose of 100mg was administered, which significantly improved the patient’s condition. Thus, this case report underscores the importance of implementing alternative treatments in patients with post-transplant autoimmune diseases, who are glucocorticoid-refractory or glucocorticoid-dependent, and highlights the effectiveness of RTX as second-line therapy.